Chronic Neuroleptic‐Induced Parkinsonism Examined With Positron Emission Tomography. Issue 7 (30th April 2020) - Galoppin, Manon; Berroir, Pierre; Soucy, Jean‐Paul; Suzuki, Yoshitaka; Lavigne, Gilles J.; Gagnon, Jean‐François; Montplaisir, Jacques Y.; Stip, Emmanuel; Blanchet, Pierre J.
Abstract: Background: Neuroleptic drug‐induced parkinsonism (NIP) is a leading cause of parkinsonism, particularly in aging. Based on abnormal dopamine transporter scan results, individuals displaying chronic NIP are often diagnosed with Lewy‐body Parkinson's disease (PD), but this assumption needs further substantiation. Objective: To quantitate the profile of striatal dopaminergic nerve terminal density in NIP relative to PD. Methods: We used the positron emission tomography ligand [ 11 C](+)‐dihydrotetrabenazine targeting vesicular monoamine transporter type 2 (VMAT2) binding sites and collected various clinical parameters (motor ratings, olfaction, polysomnography to document rapid eye movement sleep muscle activity, quantitative sensory testing for pain thresholds) possibly predicting binding results in patients older than age 50 living with schizophrenia spectrum disorders under long‐term stable antipsychotic drug treatment, with (N = 11) or without (N = 11) chart documention of chronic NIP, and compared them to healthy volunteers (N = 11) and others medicated for PD (N = 12). Results: Striatal VMAT2 binding was dichotomous in the NIP group between those with spared (N = 5) or low (N = 6) PD‐like values. Striatal binding reduction in the low VMAT2‐NIP group was asymmetric without the gradient of maximal involvement in the posterior putamen typical of PD. Anosmia was the only nonmotor parameter measured matching the abnormal striatal VMAT2 binding status. Conclusion: These preliminary observations suggest that striatal VMAT2 binding is abnormal in a fraction of chronic NIP cases and differs in spatial distribution from PD. The possibility of a drug‐induced axonopathy and resultant synaptopathy, as well as the evolution of the binding deficit, warrant further longitudinal studies in a large cohort. © 2020 International Parkinson and Movement Disorder Society